Variability in Physiological Traits Reveals Boron Toxicity Tolerance in Aegilops Species - Khan, Mohd. Kamran; Pandey, Anamika; Hamurcu, Mehmet; Avsaroglu, Zuhal Zeynep; Ozbek, Merve; Omay, Ayse Humeyra; Elbasan, Fevzi; Omay, Makbule Rumeysa; Gokmen, Fatma; Topal, Ali; Gezgin, Sait (Frontiers in Plant Science, 2021)
Boron (B) is an important micronutrient required for the normal growth and development of plants. However, its excess in soil largely damages the plant tissues affecting the final yield. Wheat which is one of the main staple crops have been reported to be largely affected by the B toxicity stress in the arid and semi-arid regions of the world. This prevalence of B toxicity stress can be addressed by utilizing the wild wheat genotypes with variant level of stress tolerance. Wild wheat relatives have been identified as a prominent source of several abiotic stress tolerant genes. However, Aegilops species in the tertiary gene pool of wheat have not been well exploited as a source of boron (B) toxicity tolerance. This study explores the root-shoot growth, proline induction, and extent of lipid peroxidation in 19 Aegilops accessions comprising of six different species and the B tolerant check wheat cultivar Bolal 2973 grown under Control (3.1 μM B); toxic (10 ppm B), and highly toxic (100 ppm B) boron stress treatment. B toxicity stress had a more decisive impact on growth parameters as compared to MDA and proline content. The obtained results suggested that even the genotypes with high shoot B accumulation can be tolerant B toxicity stress and the mechanism of redistribution of B in leaves should be studied in detail. A high level of variation in the response towards high B toxicity proposed that the studied Aegilops accessions can be potentially used for genetically improving the B toxicity tolerance trait. Though a number of accessions showed suppression in the root-shoot growth, few accessions with stress adaptive plasticity to B toxicity stress leading to improvement of shoot growth parameters could be determined. The two accessions, Ae biuncialis accession TGB 026219 and Ae columnaris accession TGB 000107 were identified as the potential genotypes with B toxicity stress tolerance and can be utilized for developing pre-breeding material in B tolerance based breeding programs.